Architectural education at Lviv Polytechnic during the interwar period - Черкес, Богдан; Лінда, Світлана; Богданова, Юлія; Cherkes, Bohdan; Linda, Svitlana; Bohdanova, Julia (Lviv Politechnic Publishing House, 2017)
У статті розглянуто історію розвитку архітектурної освіти у Львівській політехніці у міжвоєнний період. Визначено основні напрямки розвитку архітектурної освіти цього часу, проаналізовано діяльність найвизначніших представників львівської архітектурної школи.

The history of architectural education during the interwar period is presented in this article. The basic directions of an architectural education development in Lviv of this time have been determined and the activity of the most prominent representatives of the Lviv architectural school has been analyzed.
Архітектурна освіта у Львівській політехніці міжвоєнного періоду
Keywords: Львівська політехніка; архітектурний факультет; архітектор; професор; Lviv Polytechnic; Department of Architecture; architects; professors